A Highly Durable, Self-Photosensitized Mononuclear Ruthenium Catalyst for CO2 Reduction - Kamada, Kenji; Okuwa, Hiroko; Wakabayashi, Taku; Sekizawa, Keita; Sato, Shunsuke; Morikawa, Takeshi; Jung, Jieun; Saito, Susumu (Synlett, 2022)
A novel mononuclear ruthenium (Ru) complex bearing a PNNP-type tetradentate ligand is introduced here as a self-photosensitized catalyst for the reduction of carbon dioxide (CO2). When the pre-activation of the Ru complex by reaction with a base was carried out, an induction period of catalyst almost disappeared and the catalyst turnover numbers (TONs) over a reaction time of 144 h reached 307 and 489 for carbon monoxide (CO) and for formic acid (HCO2H), respectively. The complex has a long lifespan as a dual photosensitizer and reduction catalyst, due to the sterically bulky and structurally robust (PNNP)Ru framework. Isotope-labeling experiments under 13CO2 atmosphere indicate that CO and HCO2H were both produced from CO2.
Keywords: CO2 reduction; photocatalyst; ruthenium complex; carbon monoxide; formic acid